MACROCIRCULAR GRAVITATIONAL MOTION THEORY - de Almeida, Carlos Alessandro Santos (Seven Editora, 2026)
Based on the concepts of dark matter and dark energy, I present a hypothesis that all the universal energy that organizes and sustains the cosmos is manifested in macrocircular gravitational motion, as a driving force behind the movements of galaxies, which do not represent an expansive linear motion, but rather the macrocircular motion of the gravitational center. The gravitational center energy, therefore, is the organizing principle that maintains the cohesion and structure of the universe, exerting a powerful influence on everything that exists through macrocircular motion. Not necessarily in a perfect circle, but in a centrally attractive pattern. It is concluded that macrocircular gravitational motion reveals itself in a universal dynamic of circuits and patterns that we observe at all levels of reality, from stellar, planetary, and satellite orbits to the movements of subatomic particles.